2023
DOI: 10.1002/14651858.cd015244.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and dietary interventions for Ménière’s disease

Abstract: Background Ménière's disease is a condition that causes recurrent episodes of vertigo, associated with hearing loss and tinnitus. Lifestyle or dietary modifications (including reducing the amount of salt or caffeine in the diet) are sometimes suggested to be of benefit for this condition. The underlying cause of Ménière's disease is unknown, as is the way in which these interventions may work. The efficacy of these different interventions at preventing vertigo attacks, and their associated symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Investigating the potential interplay between Neurotrophin-3 and MD, as well as the specific role of Neurotrophin-3 cytokines in immune initiation and disease progression, are crucial areas for future investigation. Notably, discussions in the literature regarding targeted drugs like IL-6 targeted Siltuximab for autoimmune/autoinflammatory MD suggest the feasibility of Neurotrophin-3-targeted therapies for MD ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the potential interplay between Neurotrophin-3 and MD, as well as the specific role of Neurotrophin-3 cytokines in immune initiation and disease progression, are crucial areas for future investigation. Notably, discussions in the literature regarding targeted drugs like IL-6 targeted Siltuximab for autoimmune/autoinflammatory MD suggest the feasibility of Neurotrophin-3-targeted therapies for MD ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…c) There is insufficient evidence for the effectiveness of many other measures that have been recommended, such as life-style changes, e.g., low salt diet ( 19 ), diuretics ( 4 ), pulsed low-pressure delivery ( 20 ), surgical interventions ( 21 ), intratympanic steroids ( 22 ), and intratympanic gentamicin ( 23 ). All in all, there is very limited evidence for the efficacy of any prophylactic therapy in MD that does not impair vestibular function.…”
Section: Discussionmentioning
confidence: 99%
“…[1] However, in previous reviews, insufficient randomized controlled trials were found to provide evidence to support or refute the idea that MD should limit alcohol intake. [9,10] In addition, contrary to conventional advice, some clinical studies have shown that alcohol consumption may be negatively associated with MD, [11][12][13][14] but causal inference has remained unclear. Several studies have shown that average alcohol intake cannot fully explain the causal relationship between alcohol consumption and disease incidence, and different drinking patterns may have different effects on the occurrence and development of disease.…”
Section: Introductionmentioning
confidence: 99%